2015
DOI: 10.30935/cedtech/6148
|View full text |Cite
|
Sign up to set email alerts
|

Preservice Teachers’ Critical Thinking Dispositions and Web 2.0 Competencies

Abstract: The aim of this study was to investigate the associations between preservice teachers' Web 2.0 competencies and their critical thinking disposition (CTD). The study employed an associational research design using California Critical Thinking Disposition-Inventory (CCTD-I) and a Web 2.0 competency questionnaire including items related to Web 2.0 awareness, Web 2.0 use, and educational use of Web 2.0 tools. Five different Web 2.0 tools included in the study: (a) blogs, (b) wikis, (c) social networking websites, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0
8

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 37 publications
2
25
0
8
Order By: Relevance
“…Fostering the development of students' critical thinking is regarded as an essential outcome of higher education [4], and in some countries has become a very important part as the main goal of learning and education [5]. Teaching critical thinking to the prospective teacher has garnered attention for a while, and the role of future teachers seems more crucial than ever before for educational systems in terms of seeking improvement in critical thinking [6]. In the faculty of education and teachers training, teacher educators have to teach and give cognitive skills to prospective teacher before they train them to the students in the classroom [7], and education before becoming a teacher is proper time to intervention activities which promote their critical thinking [8].…”
Section: Introductionmentioning
confidence: 99%
“…Fostering the development of students' critical thinking is regarded as an essential outcome of higher education [4], and in some countries has become a very important part as the main goal of learning and education [5]. Teaching critical thinking to the prospective teacher has garnered attention for a while, and the role of future teachers seems more crucial than ever before for educational systems in terms of seeking improvement in critical thinking [6]. In the faculty of education and teachers training, teacher educators have to teach and give cognitive skills to prospective teacher before they train them to the students in the classroom [7], and education before becoming a teacher is proper time to intervention activities which promote their critical thinking [8].…”
Section: Introductionmentioning
confidence: 99%
“…However, since they never posted blog entries and the Web 2.0 tools that they used in content development were not directly related to blogging, they may have considered themselves less competent. In a study, Sendag, Erol, Sezgin, and Dulkadir (2015) found that the Web 2.0 tool blogging self-efficacy perceptions of pre-service teachers were one of the lowest self-efficacy levels determined. Furthermore, the authors emphasized that Turkish pre-service teachers did not frequently use blogs, wikis and podcasts in the study.…”
Section: Discussionmentioning
confidence: 99%
“…The learner reviews information, compares it with other views and then evaluates, reconstructs and reflects it. The learner is active within the learning process (Sendag et al, 2015). For this reason, it can be said that critical thinking is implemented when learning via social networks.…”
Section: Discussionmentioning
confidence: 99%